Characterization of tar generated from the mixture of municipal solid waste and coal pyrolysis at 800 °C - Tursunov, O; Suleimenova, B; Kuspangaliyeva, Botagoz; Anthony, E.J.; Sarbassov, Yerbol (Elsevier, 2020)
Nowadays, comprehensive perception of the tar characteristics generated from municipal solid waste (MSW) and coal to guide pyrolysis or gasification gas yield upgrading and cleaning has attracted massive research attention. In this study, MSW and coal samples were chosen as principal components. The mixture of these products was pyrolyzed in a horizontal tube furnace at 800 °C with a heating rate of 20 °C/min. The tar derived from the pyrolysis of this mixture was further studied. Gas chromatography–mass spectrometry (GC–MS)coupled with a trace GC and a nuclear magnetic resonance (NMR) spectrometer was applied to investigate the tar composition and characterization along with their molecular chemical structures. 1H and 13C NMR spectra indicated that the functional groups of the tar derived from the mixture of MSW and coal were dominant at the resonances of 0.9–1.8 ppm, 1.5–2.6 ppm and 3.8–4.1 ppm for 1H, 10–40 ppm and 60–80 ppm for13C. The results from GC–MS showed that the tar derived from the mixture of MSW and coal contained about 20 major chemical compounds such as benzene, methyl isobutyl, toluene, xylene, phenol, cresol, naphthalene and others.